Metode Weighted Product Untuk Pendukung Keputusan Penilaian Pencemaran Udara Berdasarkan Limbah Gas dan Kualitas Udara Ambien - Wiedya Putri Hartarani; Wildan Mahmud; Ery Mintorini (Jurnal Teknik Informatika dan Sistem Informasi, 2019)
This study aims to determine the level of air pollution based on gas waste and ambient air quality, so it can be known which chimney releases waste gas the most and the least. It also knows which villages are most affected and safest from gas waste from PG Mojopanggung. Weighted Product method is used to calculate the level of air pollution. The results showed that from the side of the gas waste, the Stork I Boiler Chimney is the most discharging chimney gas waste, while the value of pollution by chimney kettle in PG Mojopanggung all does not exceed the standard quality that has been determined. Conversely, in terms of ambient air quality, Jatimulyo village is the village most affected by gas waste from PG Mojopanggung. There are some air pollutants that exceed the specified quality standard but not too much difference. To overcome the air pollutant that exceeds the quality standard, PG Mojopanggung performs the gas waste treatment and several other solutions.